Finding and tracking targets in the wild: Algorithms and field deployments - Isler, Volkan; Noori, Narges; Plonski, Patrick; Renzaglia, Alessandro; Tokekar, Pratap; Vander Hook, Josh (SSRR 2015 : 2015 IEEE International Symposium on Safety, Security, and Rescue Robotics : Purdue University, West Lafayette, Indiana, USA, October 18-20, 2015, 2015)
We describe our efforts on building a robotic system for detecting and tracking radio-tagged invasive fish using teams of autonomous ground and surface vehicles. In addition to system building and field experiments, our efforts clustered around three fundamental problems: (1) Search: how to find the target as quickly as possible, (2) Active localization: how to actively choose measurement locations to accurately estimate target locations, and (3) Long-term autonomy through energy-efficiency and harvesting. We present specific problem formulations and a summary of our results so far. We conclude the paper with a discussion on our progress and next steps.